Biotechnology Cultivation of Medicinal Plants - qizi, Ismoilova Dilnoza Zubayd (American Journal of Biodiversity, 2024)
This article describes the medicinal properties of plants growing in the territory of Bukhara, and the experience of growing some medicinal plants in the region.